Remote monitoring using the keras library - Kashaganova, G. B.; Ilakhunov, P. Kh. (Харківський національний автомобільно-дорожній універститет, 2024)
This article discusses the use of modern technologies, including mobile applications and neural networks, for remote patient monitoring. Various applications of artificial intelligence in medicine are described, such as real-time monitoring, diagnostics, personalized treatment, and remote consultation. Particular attention is paid to the use of mobile device cameras in medical applications for video consultations, symptom recognition, disease monitoring, and patient response analysis. An example code for image classification using deep neural networks is provided. The final part of the article discusses the importance of using mobile health with neural networks for remote patient monitoring and predicting possible complications.
Keywords: mobile applications; medical monitoring; artificial intelligence; neural networks; remote diagnostics; video consultations; symptom recognition; personalized treatment; remote consultation; deep learning; image classification; patient health; 004